The need for marketing management in the management of the company’s activities. (Journal of Economic Research & Business Administration, 2016)
Today one of the most topical issues in the management of the enterprise is the use in the management of marketing management, management firms based on the principles and tools of marketing. Marketing has become a vital component of business success. Unfortunately, many domestic companies do not realize the importance to the proper level marketing management in the management of the company. Marketing management – a new science. Marketing management was first used in 1999 by Royal Bank of Canada, as a result of the reorganization of the company. As a result, over the next 3 years of income of the bank increased by 1 billion dollars. Under the influence of a number of important trends and forces in the commercial organizations is the introduction of new beliefs and change. The subjects of the market completely rethink their philosophy and concept. In total there are 14 marketing management major changes implemented far-sighted companies in the XXI century. Success will be those companies that are able to implement these changes in the company.
Keywords: marketing management; principles and tools of marketing; consumers; needs; 14 marketing management major changes.